Do Teachers’ Beliefs Turn to Practice? Countryside Secondary School Science Teachers’ Teaching Beliefs, Scientific Epistemological Beliefs, and Approaches to Teaching - Reymund Derilo (Journal on Efficiency and Responsibility in Education and Science, 2025)
This study employed a convergent parallel mixed-method design to examine the teaching beliefs of secondary school teachers and determine the relationship between their scientific epistemological beliefs and pedagogical approaches. Semi-structured interviews were utilized to explore teachers’ teaching beliefs, while quantitative analysis involved a descriptive-correlational approach, employing two adapted questionnaires: Scientific Epistemological Belief Questionnaire (SEBQ) and Approaches to Teaching (ATI). Analysis of interview responses reveals that most teachers prioritize creating a student-involved classroom environment, typically teacher-initiated learning, rather than allowing student-led initiatives. They generally view themselves as facilitators of learning, base their teaching decisions on the curriculum, and believe that students demonstrate understanding by reiterating what has been taught. Quantitative analysis indicated that science teachers in the region largely demonstrate traditional beliefs regarding the origins and characteristics of scientific knowledge while predominantly employing transitional teaching approaches in their practice. Furthermore, the study found a correlation between teachers' SEBs and adopting learner-focused teaching approaches. Integration and meta inference of qualitative and quantitative findings bear significant implications for science education, suggesting avenues for enhancing, restructuring, and reforming teachers' teaching and epistemological beliefs. Hence, efforts should focus on fostering teachers' deeper understanding of the nature of science.